E- LEARNING IS ONE OF SOLUTION OF LEARNING PROCESS IN PANDEMIC SITUATION - Nelvia Ibrahim (JISOS: JURNAL ILMU SOSIAL, 2023)
This article presents the background of the educational process during the pandemic, one of which is by using electronic learning in various forms such as Google Classroom, Google Meet, Zoom, Skype, OBS and many other forms of electronic learning. This learning is divided into two synchronous and asynchronous. Synchronous is learning in a network that requires media to assist learning such as computers, note books, android and also the internet or network, while Asynchronous is learning that is carried out directly by teachers and students at school or face to face. Thus electronic learning is very helpful for pandemic citizens but this learning is more flexible and can be used at any time depending on specific aims and objectives